Being Eurasian : memories across racial divides - Lee, Vicky (Meiqi) (Hong Kong University Press, 2004)
Includes excerpts from: Looking at the stars / Joyce Symons ; Stanley : behind barbed wire / Jean Gittins ; Intercultural reminiscences / Irene Cheng.